Thermodynamic, economic and environmental analyses of novel solar-powered ejector refrigeration systems - Yadav V.K.; Sarkar J.; Ghosh P. (My University, 2025)
The performance of an ejector refrigeration cycle can be improved by recovering expansion energy from condenser to evaporator using an additional two-phase ejector, but yet to be explored. Hence, two novel solar-driven ejector refrigeration systems are investigated on the basis of energy, exergy, economy and environmental aspects. The investigated systems are driven by an evacuated tube collector and modified by using an additional ejector for recovery of expansion energy. The impact of various operating circumstances on the performance parameters is explored and compared with the traditional (basic) solar-driven ejector refrigeration system. Effects of various component efficiencies and seasonal climatic conditions are studied as well. Various working fluids are tried for both systems and R152a is ultimately determined to be the best option. Within proposed cycles, Cycle-2 yields better performances as compared to Cycle-1. The total specific cost and mass of CO2 emission are minimum for Cycle-2, which are 17.4% and 11% lower than that of the basic cycle, respectively. The ejector efficiencies are more sensitive as compared to other component efficiencies. The study reveals that the proposed novel cycles have around 10–18% enhancement in the overall coefficient of performance and yield the best performance in month of April. © 2022 Elsevier Ltd